2017
DOI: 10.1007/s00268-017-4412-x
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Hybrid NOTES Cholecystectomy: A Single‐Centre Long‐Term Experience on Sexual Function

Abstract: The findings show that transvaginal hybrid NOTES cholecystectomy is a safe procedure for female patients, particularly with regard to sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…On the other hand, data has been published about postoperative sexual function after transvaginal surgery. In a median follow-up of 40 months after TVC, Pohlen et al did not find any impairment of the female sexual function [12]. Our previous studies support these results with a follow-up of 6 as well as 24 months postoperatively [13,14].…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, data has been published about postoperative sexual function after transvaginal surgery. In a median follow-up of 40 months after TVC, Pohlen et al did not find any impairment of the female sexual function [12]. Our previous studies support these results with a follow-up of 6 as well as 24 months postoperatively [13,14].…”
Section: Discussionsupporting
confidence: 84%
“…Some scholars declare that [25,26] traditional vaginal hysterectomy does not affect female sexual function. A self-control study on pre-and post-vNOTES cholecystectomy also shows that vNOTES has no effect on female sexual function [7]. On the contrary, Sener et al [10] believe that sexual function can decline after vNOTES nephrectomy and suggest that postoperative nursing should include some methods for restoring sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, studies showed no significant difference in safety of NOTES compared to standard laparoscopic cholecystectomy. 9,15-17…”
Section: Introductionmentioning
confidence: 99%
“…14 In addition, studies showed no significant difference in safety of NOTES compared to standard laparoscopic cholecystectomy. 9,[15][16][17] Even though feasibility and safety of hybrid NOTES transvaginal cholecystectomy (TVC) are proven, expert opinions differed widely on NOTES, and its implementation was controversially discussed over the last years. Critics were encouraged by the fact that the use was limited to a few highly specialized centers, concerning restrictions in training, higher costs, and extended operation time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation